Analysis of the apoplast fluid proteome during the induction of systemic acquired resistance in Arabidopsis thaliana - Shuna Jiang; Liying Pan; Qingfeng Zhou; Wenjie Xu; Fuge He; Lei Zhang; Hang Gao (PeerJ, 2023)
Background Plant-pathogen interactions occur in the apoplast comprising the cell wall matrix and the fluid in the extracellular space outside the plasma membrane. However, little is known regarding the contribution of the apoplastic proteome to systemic acquired resistance (SAR). Methods Specifically, SAR was induced by inoculating plants with Pst DC3000 avrRps4. The apoplast washing fluid (AWF) was collected from the systemic leaves of the SAR-induced or mock-treated plants. A label free quantitative proteomic analysis was performed to identified the proteins related to SAR in AWF. Results A total of 117 proteins were designated as differentially accumulated proteins (DAPs), including numerous pathogenesis-related proteins, kinases, glycosyl hydrolases, and redox-related proteins. Functional enrichment analyses shown that these DAPs were mainly enriched in carbohydrate metabolic process, cell wall organization, hydrogen peroxide catabolic process, and positive regulation of catalytic activity. Comparative analysis of proteome data indicated that these DAPs were selectively enriched in the apoplast during the induction of SAR. Conclusions The findings of this study indicate the apoplastic proteome is involved in SAR. The data presented herein may be useful for future investigations on the molecular mechanism mediating the establishment of SAR.